Contextualizing Mapasabatu Local Wisdom in the Development of Teaching Materials for Educational Institutions in Tolitoli District - Sudaryati, Sri; Ibadurrahman, Ibadurrahman; Utomo, Jepri; Mutmainnah, Inayatul (Universitas Tanjungpura, 2025)
With an emphasis on incorporating the values of solidarity, togetherness, mutual cooperation and social empathy into the curriculum and teaching strategies at various levels of education, this research seeks to contextualize Mapasabatu local wisdom in the creation of educational materials in Tolitoli Regency. Data collection was carried out using a qualitative approach to understand the local wisdom of Mapasabatu and the potential for its integration in teaching materials. Data was collected through direct observation, interviews with the Department of Education and Culture, cultural experts, community leaders, teachers, students, as well as a review of related literature. Content analysis was used to identify relevant Mapasabatu elements. Initial teaching materials were prepared, validated by experts, and tested in Tolitoli schools. Feedback from educators and students is used to improve teaching materials, ensuring their effectiveness and relevance. The results show how contextual techniques, folklore, and digital media can be used to incorporate Mapasabatu values into learning. These teaching resources enhance social ideals and increase student engagement. Based on research findings, it is concluded that Mapasabatu Local Wisdom is effective in developing teaching materials, strengthening students' character, increasing their involvement, and teaching social values in learning.